Cercospora leaf spot management with nitrogenous fertilizers in cotton is dependent on the disease amount in the plant canopies - Parrales-Rodríguez, Víctor F. (2024)
The aim of this study was to examine the impact of both organic and inorganic nitrogen fertilizers on the intensity and epidemiological components of Cercospora leaf spot across three different canopies of cotton plants, specifically the variety DP ACALA 90, under field conditions. Fertilizers used in the study included bovine manure, Jatropha curcas seedcake, poultry manure, and urea (the latter serving as a control). These were applied at 20 days after plant emergence and then during the flowering stage until the total nitrogen (N) dose reached 50, 100, 150, or 200 kg N per hectare. The incidence and severity of the disease were assessed starting at the reproductive stage B1 (the first visible flower bud) across the lower, middle, and upper canopies of four cotton plants, with six evaluations conducted over time. To calculate the initial inoculum (Y0) and the disease progress rate (r), the Exponential, Gompertz, and Logistic models were employed based on temporal data. The study was designed as a randomized complete block with a 4x4 factorial arrangement (fertilizer type x dose), and mean comparisons were made using Tukey's test (p ≤ 0.05). It was found that disease intensity within each canopy level varied in response to the type of nitrogen source and the applied dose, with the severity of the disease (including the area under the disease progress curve) being particularly influenced. A significant interaction between the type of fertilizer and the dose regarding the intensity of Cercospora leaf spot was observed. The Exponential model most accurately depicted the disease's temporal progression. Notably, poultry manure and urea were the fertilizers that most adversely influenced the intensity and initial inoculum (Y0) of Cercospora leaf spot across the various canopies of the cotton plants. The findings suggest that the use of organic fertilizers in cotton cultivation could represent a viable sustainable management strategy.